A national survey of anaesthetists' preferences for their own end of life care. (December 2020) - Blackwood, Douglas H.; Vindrola-Padros, Cecilia; Mythen, Monty G.; Columb, Malachy O.; Walker, David
Abstract: Objectives: To describe individual views, wishes, and preferences for end of life care and to report UK anaesthetists' personal perspectives. Methods: The 'bigconversations' questionnaire was developed by modifying an existing framework for end of life discussions. An online cross-sectional survey of UK anaesthetists was then conducted using the questionnaire in January 2019. Results: The bigconversations questionnaire was validated as measuring the important aspects of end of life care by an expert panel and was found to have moderate test–retest reliability. Responses were received from 760/1913 (40%) of those invited to take part. Overall, 698/760 (92%) of respondents wished to be well informed about their condition and prognosis and 518/760 (68%) wanted to be heavily involved in decision-making about their health. Meanwhile, 639/760 (84%) of respondents would choose to forego treatment aimed at prolonging life should that life be of poor quality. The desire to spend time with family was a theme which arose from the qualitative analysis. Conclusion: This study provides the first systematic description of UK doctors', specifically anaesthetists', personal preferences for end of life care. Broad trends were identified: to be well informed; to avoid high-intensity medical treatments if terminally unwell; to spend remaining time with family and friends; and to be symptom-free and well cared for. However, a substantial minority expressed different, indeed opposite, opinions. This variation highlights that good quality end of life care must be driven by discussion of an individual's values, wishes, and preferences.